Design and Development of an Integrated Chemical Accident System for Monitoring Risk Potential of Hazard Installation - El-Harbawi, Mohanad M-A. (2006)
Mathematical models are extremely useful tools to predict the impacts of chemical process accidents. The applications of these models require competency in mathematics and computer programming. Therefore the procedural and methodology for the calculation of consequences and risks from installations handling toxic or flammable materials have been computerized by using a software called the Simulation of Chemical Industrial Accidents (SCIA). The SCIA software was successfully developed using Visual Basic (VB) programming language with integration of GIS tools. The explosion, fire and toxic release models are implemented in an interactive VB environment.